2017
DOI: 10.3390/ijerph14080911
|View full text |Cite
|
Sign up to set email alerts
|

Health Risks Awareness of Electronic Waste Workers in the Informal Sector in Nigeria

Abstract: Insight into the health risk awareness levels of e-waste workers is important as it may offer opportunities for better e-waste recycling management strategies to reduce the health effects of informal e-waste recycling. Therefore, this study assessed the knowledge, attitude, and practices associated with occupational health risk awareness of e-waste workers compared with a control group (butchers) in the informal sector in Nigeria. A cross-sectional study was used to assess health risk awareness of 279 e-waste … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
62
1
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(69 citation statements)
references
References 25 publications
4
62
1
2
Order By: Relevance
“…The sample appeared to be knowledgeable that their work carries health risks. Our finding that low risk perception is associated with non-use of PPE mirrors findings from studies of waste workers in Nigeria 34 , India 9 and Thailand. 10 Interestingly, our study did not show any association between the prevalence of injury and non-use of PPE unlike other studies which have shown higher odds of injury in those not using PPE.…”
Section: Discussionsupporting
confidence: 84%
“…The sample appeared to be knowledgeable that their work carries health risks. Our finding that low risk perception is associated with non-use of PPE mirrors findings from studies of waste workers in Nigeria 34 , India 9 and Thailand. 10 Interestingly, our study did not show any association between the prevalence of injury and non-use of PPE unlike other studies which have shown higher odds of injury in those not using PPE.…”
Section: Discussionsupporting
confidence: 84%
“…This finding is significantly higher than what had been reported by some researchers who found that only 43% of e-waste workers had awareness of the health hazards associated with e-waste from three locations in Nigeria. 24 However, this finding compares with the awareness level of 70% among butchers also found by the same researchers in the same locations. 24 The reason for this paradoxically lower awareness among the e-waste workers is not known.…”
Section: Discussionmentioning
confidence: 43%
“…24 However, this finding compares with the awareness level of 70% among butchers also found by the same researchers in the same locations. 24 The reason for this paradoxically lower awareness among the e-waste workers is not known. It could be that their desire to earn a living from e-waste business had led to their feigning ignorance of the health hazards associated with e-waste handling.…”
Section: Discussionmentioning
confidence: 43%
“…The metal concentration at the burning sites were also higher than the concentration reported in studies in China (Yekeen et al, 2016;Awasthi et al, 2016a). This is more disturbing as majority of the e-waste workers are unaware of the health risks associated with their jobs (Ohajinwa et al, 2017). Our results show an urgent need for action to stop open burning of e-waste and to reverse/stop the environmental deterioratation as a result of informal e-waste recycling.…”
Section: Implications Of High Metals Concentrations In the Environmentcontrasting
confidence: 58%